Persistence and Expansion of Guerrilla Activities: the case of Columbia - Zuleta, Hernando (Journal of Income Distribution®, 2004)
In this paper I present a dynamic model that provides an explanation for why violent movements arise, why armed conflicts can persist over long periods, why guerrilla movements operate in rich places, and whether or not redistributive policies can eliminate the incentives for guerrilla movements. I analyze these questions using a model of competitive markets, three inputs and two types of agents. Apart from the standard results, I find that: (i) The existence of guerrilla movements increases wages in the short run but reduces them in the long run. (ii) If workers or guerrilla members benefit from learning by doing, the persistence of the conflict leads to an endogenous heterogeneity that increases the difficulties of eliminating the incentives for guerrilla activity. (iii) Once in place, guerrilla activity flows to the most productive economies together with labor and capital.